Performance Evaluation of the Spiral Water Turbine - Bahtiyar, Siti Nurhajar; Mohd, Sofian (Progress in Aerospace and Aviation Technology, 2024)
Water is a fundamental component of renewable energy and may produce power through the utilization of a water turbine. These turbines utilize electromechanical energy converters to harness the kinetic energy of flowing water. The research seeks to enhance and evaluate the existing spiral water turbine design, in addition to assessing the turbine's power production via testing. The mechanism and control system were analyzed, and a comprehensive design of the water turbine was created in SolidWorks. The testing was conducted at the Sungat Bantang waterfall, with evaluations performed at heights of 0.21m, 0.51m, and 0.87m. The turbine experienced two modes of operation: half-submerged and fully submerged. The analysis of the findings is based on data collected during testing, which includes water velocity, current, voltage, and power output. The findings indicated that power output increases with water velocity as a result of increased kinetic energy in the flow. In the trials, the turbine's power output reached 28.99 W, 176.77 W, and 357.11 W under partially submerged conditions, corresponding to water velocities of 2.03 m/s, 3.16 m/s, and 4.13 m/s, respectively. Simultaneously, fully submerged conditions produced power outputs of 29.74 W, 132.34 W, and 312.34 W, respectively. Consequently, higher velocity results in increased power. In conclusion, although it was tested just at the rapid's minimal height of one meter, the turbine effectively generated energy.